Amino Acid Profiling and Chemometric Relations of Black Dwarf Honey and Bee Pollen - Sommano, Sarana Rose; Bhat, Farhan M.; Wongkeaw, Malaiporn; Sriwichai, Trid; Sunanta, Piyachat; Chuttong, Bajaree; Burgett, Michael (Frontiers in Nutrition, 2020)
To understand the amino acid patterns of by-product of A. andreniformis, this research was done to characterise the honey and bee-pollen samples from 5 colonies on the basis of their morphology, proximate composition and amino acid analysis. The pollen gains of the sampling colonies revealed variations in their structure, symmetry and sculpture. The exile surfaces of the pollens showed psilate, scabrate, clavate and echinate types of morphology. Total amino acid content of black dwarf honey bee collected pollen (150 mg/g) was found significantly higher than those of honey (15 mg/g) from the same colony. Threonine, phenylalanine and leucine were among the highest essential amino acid types found in the analysed pollen and honey samples. The proline content in black dwarf honey bee pollen and honey was found lowest than other amino acid types. The moisture content of the honey samples used in this research were found to exceed the limit as prescribed by Codex Alimentarius Commission (<20%). The ash content of the analysed samples were mostly within the limits (< 0.6%) prescribed by international norms. The fat contents of the pollens varied from 5.01 to 5.05 % and the honey showed zero fat content. The carbohydrate content in the honey samples were found to differ significantly from each other maximum content (73.16%) and the lowest carbohydrate content was 67.80%. The pollen and honey samples were found to have positive effect on in vitro digestibility of proteins.